Synchronous Papillary Thyroid Cancer and Lymph Node Tuberculosis in a Patient with Cervical Lymphadenopathy: Case Report and Review - Velasco, José A.; Jaimes, Edwing M.; Tovar, Mariano P.; Reyes, Greta G.; Martinez, Saul J.; Mata, Carlos J.; Monroy, Miguel A.; Bustamante, Ludwigvan A. (International Journal of Innovative Research in Medical Science, 2022)
The incidence of thyroid cancer has increased in the last decade, with a mortality rate of 0.5 per 100,000 inhabitants, being papillary carcinoma as the most common histological type. Identify it synchronously with a case of lymph node tuberculosis (TBG) is extremely rare and a real challenge for its diagnostic suspicion. Tuberculous lymphadenitis is clinically indistinguishable from metastatic forms of papillary thyroid carcinoma and histopathologic examination is the most accurate test for diagnosis. In this paper we present the case of a 31-year-old male who presented cervical lymphadenopathy and a concomitant thyroid nodule, giving the impression of a metastatic thyroid tumor, who received treatment with total thyroidectomy and cervical lymph node dissection.